Importancia da natação para desenvolvimento motor de crianças de 3 a 5 anos de idade - Tomazeli, Angélica (My University, 2019)
Swimming is one of the most indicated sports for its benefits in different aspects, such as locomotor, cardiorespiratory and social, among others. Child swimming plays a fundamental role in the health of children, because it contributes to the maturation of the nervous system, the child will better dominate his body in space, in time and refining his motor coordination. OBJECTIVE: is to analyze the importance of swimming in the motor development of children aged 03 05 years from the application of the battery of tests of Gallahue and Ozmun (2005). METHODS: Twenty children practicing and not practicing swimming were submitted to the study, the 5 locomotion and 5 manipulative tests were applied. RESULTS: After performing the 2 weeks of tests, the children presented distinct results in relation to the following activities of sliding and horizontal jump, children who practice swimming have better results than children who do not practice the sport. The age of the child also interferes with the results. CONCLUSION: The children practicing swimming participants in the study present better performance in the tests than those who do not practice the modality, representing as soon as swimming contributes effectively to motor development (sic).
A natação é um dos esportes mais indicados pelos seus benefícios em diferentes aspetos, como locomotor, cardiorrespiratório, social, dentre outros. A natação infantil tem papel fundamental na saúde das crianças, pois contribui com o amadurecimento do sistema nervoso, a criança vai dominando melhor o seu corpo no espaço, no tempo e refinando a sua coordenação motora. OBJETIVO: é analisar a importância da natação no desenvolvimento motor de crianças de 03 05 anos a partir da aplicação da bateria de testes de Gallahue e Ozmun (2005). METODOLOGIA: Foram submetidos a pesquisa 20 crianças praticantes e não praticantes de natação, Foram aplicados os 5 testes de locomoção e 5 manipulativos. RESULTADOS: Após realizar as 2 semanas de testes, as crianças apresentaram resultados distintos com relação as seguintes atividades. Deslizamento e Salto horizontal, crianças que praticam natação apresentam resultados bem melhores que crianças que não praticam o esporte. A idade da criança também pode interferir nos resultados. CONCLUSÃO: As crianças praticantes de natação participantes do estudo apresentam melhor desempenho nos testes do que as que não praticam a modalidade, representando assim que a natação contribui de forma efetiva para o desenvolvimento motor (sic).
Keywords: Natação para crianças; Capacidade motora em crianças